Analysis of The Dynamics of Property Value Fluctuations in The Special Region of Yogyakarta - Saleh, Rahmat; Yuniarti, Dini (UMSurabaya Publishing, 2024)
The purpose of this study is to determine and identify the influence of physical property characteristics such as land area and building area; property legal characteristics in the form of property ownership rights; environmental characteristics in the form of designation zones on property values in D.I.Yogyakarta and apply the best equation method model in determining the value of large quantities of property in addition to the market approach method and cost and income approach. Access to research observation data in the form of primary data obtained in several ways, namely telephone interviews, personal interviews directly with property owners, and secondary data accessed by desk research of the DJTR spatial plan of the Ministry of ATR BPN, data access using purposive sampling models with non-probability sampling techniques, the number of observations as much as 135 data used. The research method uses multiple regression analysis ordinary least square method with Eviews 10 analysis tools, the form of the research regression model function using the selection of statistical criteria, applying the positivism paradigm with quantitative data in the form of Analytical survey, Identification of linear relationship behavior using the Mac Kinnon Test, and White Davidson MWD, Statistical criteria test in the form of F test, t-test, Determination Coefficient Test (R2), Economic criteria test is applied to compare between the estimated parameter coefficients by economic theory, Classical Assumption Test using Normality, Linearity, Multicollinearity, and Heteroscedasticity Test. The results showed that the findings of property characteristics simultaneously or simultaneously on the variables of land area, building area, ownership rights, and designation zone significantly affect property values with a coefficient of determination level of 68.69%. Partially or individually, the findings revealed the influence of the characteristics of land area, building area, ownership rights, and designation zone positively and significantly on property values. Selection of the best model of the regression function equation, applying the log-log regression equation model in determining property value